First record of Gardnerycteris keenani in the North Pacific of Costa Rica and southern range extension of Artibeus inopinatus - Ramírez-Vargas, Marco Antonio; Granados-Madrigal, Gabriel; Leiva-Méndez, Marck; Piedra-Chacón, Rotney (Therya Notes, 2025)
The National Ecological Monitoring Program (PRONAMEC) of the National System of Conservation Areas (SINAC) in Costa Rica aims to generate scientific information for biodiversity management in Protected Wildlife Areas. In 2023, the first structured bat survey was conducted in 4 protected areas of the Tempisque Conservation Area (ACT), recording Gardnerycteris keenani for the first time in the North Pacific of Costa Rica and the southernmost record of Artibeus inopinatus. Between July and October 2023, 6 mist nets were set up in the Iguanita National Wildlife Refuge (RNVSI), Guanacaste. The nets were placed at two sites: “Sendero Manglar” and “Quebrada Grande”, covering mangroves and deciduous dry forests areas, accomplishing a survey effort of 101.6 net-hours. An adult male Gardnerycteris keenani was recorded on July 14 and an adult female Artibeus inopinatus on October 16, both in good health. The finding of Gardnerycteris keenani extends its known distribution in Costa Rica, while the discovery of Artibeus inopinatus reinforces its association with tropical dry forests. These records highlight the ecological importance of the RNVSI and reveal information gaps due to limited previous sampling efforts. The presence of these species underscores the need to continue monitoring programs to support management decisions, especially in the face of anthropogenic threats.